Stretching the peace: The role of Kundalini yoga in the lives of young people in Alexandra, South Africa - Kaehkoenen, S.; Silva, R. da. (Journal of Humanistic Psychology, 2025)
The purpose of this exploratory study was to underline the importance of a humanistic approach to peace studies against a scenario characterized by the failings and weaknesses of the liberal peacebuilding agenda. To do so, we employ a transrational peace research framework to investigate whether Kundalini yoga can be used as a peacebuilding tool by analyzing its role in the lives of young people living in an Alexandra township, in South Africa. We conducted semistructured interviews with yoga instructors, surveyed yogis online, and analyzed three annual reports of Yoga4Alex, an organization that provides young people in Alexandra with tools for a better life through Kundalini yoga (and other programs). The main findings of this study demonstrate that practicing Kundalini yoga plays a vital role in the yogis’ lives in Alexandra, creating a space where peace can grow. Many respondents consider that yoga creates a community that offers them support and mental well-being. Moreover, yoga practice helps to develop tools they can use for personal transformation, contributing to the creation of a new identity and offering a nonviolent alternative for everyday life. This study provides reflections for both research and practice.